Istifham Nonliteral dan Fungsi Retorisnya dalam Surah Ṭāhā dan Al-Anbiyā': Kajian Balaghah tentang Khurūj al-Istifhām ‘An Muqtadhā al-Ẓāhir - Nesa Oktavia Toligaga; Chaterina P. Doni; Sriwahyuningsih R. Saleh; Randi Safii (Universitas Palan, 2026)
This study aims to analyze the forms and functions of balaghah istifham that deviate from their original meaning (khurūj al-istifhām ‘an muqtadhā al-ẓāhir) in Surah Ṭāhā and Surah al-Anbiyā’. The study employs a descriptive qualitative approach using content analysis. The research data consists of all verses containing the istifham style in both surahs. Data collection was conducted through the identification, classification, and interpretation of verses based on the theory of ma‘ānī. The results show that there are 45 forms of istifham distributed across both surahs, comprising 20 forms in Surah Ṭāhā and 25 forms in Surah al-Anbiyā’. Most of the istifham forms identified fall under the category of figurative (istifham majazi), while literal (istifham hakiki) forms appear only in certain verses. The dominant rhetorical functions include al-inkār, al-taqrīr, al-taubīkh, al-tahdīd, al-tašwīq, al-‘arḍ, and al-‘itāb. These findings indicate that the use of interrogative sentences in both surahs does not merely serve as a tool for asking questions, but also functions as a rhetorical instrument to construct arguments, affirm doctrinal messages, and strengthen the persuasive and educational effects of the Qur’an.